2020
DOI: 10.1093/jamia/ocaa216
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of telehealth users in NYC for COVID-related care during the coronavirus pandemic

Abstract: The response to COVID-19 has involved an unprecedented expansion in telehealth. While older Americans and minority populations among others are known to be disadvantaged by the digital divide, few studies have examined disparities in telehealth specifically, and none during COVID-19. This study uses data from a large health system in NYC – the initial epicenter of the US crisis – to describe characteristics of patients seeking COVID-related care via telehealth, ER, or office encounters during the peak pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
135
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 9 publications
6
135
1
Order By: Relevance
“…This was based solely on race/ethnicity, despite no significant difference in primary languages spoken between the timeframes. This is in contrast to a similar study in a large health system in New York City, which demonstrated Black/African American and Hispanic/Latino patients have lower odds of using telemedicine in comparison to White or Asian patients [ 27 ]. These disparities have been explained by lack of digital access, digital literacy, and mistrust of the telemedicine system.…”
Section: Discussioncontrasting
confidence: 99%
“…This was based solely on race/ethnicity, despite no significant difference in primary languages spoken between the timeframes. This is in contrast to a similar study in a large health system in New York City, which demonstrated Black/African American and Hispanic/Latino patients have lower odds of using telemedicine in comparison to White or Asian patients [ 27 ]. These disparities have been explained by lack of digital access, digital literacy, and mistrust of the telemedicine system.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study is the first to examine disparities in telemedicine use for subspecialty diabetes care during the pandemic. However, analyses of care delivery to primary care populations during the same time frame also concluded that older adults, 3,12 patients with non-English language preferences, 3,12 and those with public insurance 12 were less likely to receive care after widescale implementation of telemedicine, suggesting these associations are robust.…”
Section: Discussionmentioning
confidence: 99%
“…7,[36][37][38] These findings are consistent with the existing literature, which largely suggests that being younger, white, higher income, and female are associated with higher utilization of telemedicine. 34,35,39,40 However, these patterns appear to vary by institution and patient population. 41,42 Differing patterns and associations, however, are not surprising given the variations in study setting, telemedicine intervention, patient population, specialty line, and data analysis plan among telemedicine studies, which makes comparing single-institution studies challenging.…”
Section: Discussionmentioning
confidence: 99%